Procedural Results and In-Hospital Adverse Outcomes Following Multivessel Percutaneous Coronary Intervention (PCI) - Hoque, Md Harisul; Rahman, Sufia; Siddique, Md Abu; Ahsan, Syed Ali; Ahmed, CM; Zaman, SM Mustafa; Mahmood, Manzoor; Rahman, Mukhlesur; Ahmed, Md Khurshed (University Heart Journal, 2010)
Several Studies have reported specific factors associated with increased risk of adverse outcome following balloon angioplasty. These factors include advanced age, female Sex, unstable angina, congestive heart failure, diabetes and multivessel Coronary artery disease. By this time, Studies have been shown the remarkable procedural success & minimum adverse outcomes following multivessel stenting. This comparative observational study shows no death, procedural MI, tamponade, cerebrovascular accident, heart failure or cardiogenic shock, vascular access site complications like bleeding, A-V fistula in any group (single vessel stenting vs multivessel stenting). However, minor adverse events occurred at an overall rate of 6% in single vessel stenosis (SVS) group & 12% in multivessel stenosis (MVS) group. Procedural results were also similar in both groups. Angiographic success of 100% in the SVS group & 98% in the MVS group noted. The difference in the outcomes were between the two groups was not significant. Key Words: Adverse Outcomes; Multivessel Coronary Stenting; Procedural Results DOI: 10.3329/uhj.v5i2.4557 University Heart Journal Vol.5(2) July 2009 pp.66-70